Analisis Bauran Pemasaran terhadap Penjualan Regina Beauty Care: Studi Kasus CV Regina Kosmetika Mandiri - Yuni Indah Sar; Lia Nirawati (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine the analysis of the marketing mix on the purchasing decision of Regina Beauty Care (case study of CV Regina Kosmetika Mandiri). This type of research is a descriptive qualitative research. Determination of informants is done by taking key informants with purposive techniques or techniques for determining informants based on certain considerations, usually related to the scale of involvement, knowledge, and authority of a person with the object of research. In this study, the tool used to identify and compile the factors of the online shop 'Regina Beauty Care' strategy was using SWOT analysis. The results of this study indicate that the marketing strategy used is by using the 4P marketing mix, namely product, price, place, promotion. Through IFAS and EFAS analysis, it can be seen that Regina Beauty Care has a strength score of 1.99, a weakness score of 0.63, an opportunity score of 1.83 and a threat score of 0.82. Based on the results of the IFAS and EFAS analysis as well as the SWOT analysis diagram which shows the right results in quadrant I (one). Keywords: Marketing Mix, Sales